1992
DOI: 10.1159/000113899
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behavior and 2-Deoxyglucose Uptake in Male Red-Sided Gaiter Snakes <i>(Thamnophis sirtalis parietalis)</i>

Abstract: The [14C]2-deoxygIucose (2-DG) technique was used to study patterns of neural activity associated with the species-typical courtship behavior of male red-sided garter snakes (Thamnophis sirtalis parietalis). Males in this species court females intensely during the first month following spring emergence from their prolonged winter hibernation. Autoradiographic methods were used to measure the accumulation of radioactive label in various regions through the brains of male garter snakes that courted fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…The absence of any relationship between brain nucleus size and behavior in the red-sided garter snake does not mean that brain-behavior relationships at the level of the individual cannot be detected. Individual variation in brain metabolism as measured by 2-deoxyglucose utilization correlates well with the level of sexual activity exhibited by male red-sided garter snakes (Allen and Crews, 1992); perhaps significantly, males with greater 2-deoxyglucose utilization in limbic nuclei tended to be courters. Gahr (1990) demonstrated that in the canary, seasonal fluctuations in Nissl staining are not correlated with the patterns of immunoreactivity using the estrogen receptor antibody H222.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The absence of any relationship between brain nucleus size and behavior in the red-sided garter snake does not mean that brain-behavior relationships at the level of the individual cannot be detected. Individual variation in brain metabolism as measured by 2-deoxyglucose utilization correlates well with the level of sexual activity exhibited by male red-sided garter snakes (Allen and Crews, 1992); perhaps significantly, males with greater 2-deoxyglucose utilization in limbic nuclei tended to be courters. Gahr (1990) demonstrated that in the canary, seasonal fluctuations in Nissl staining are not correlated with the patterns of immunoreactivity using the estrogen receptor antibody H222.…”
Section: Discussionmentioning
confidence: 73%
“…Lesion of the NS, on the other hand, facilitates courtship behavior (Krohmer and Crews, 1987b), suggesting that the POA is under inhibitory control ofthe NS. Using 2-deoxyglucose to monitor patterns of neural activity in the brain, Allen and Crews (1992) found that the POA and the NS in courting males were more active than in noncourting males.…”
mentioning
confidence: 99%
“…If the AME is functionally analogous to the MeP and the NS is analogous to the MeA, then NS lesions should lead to greater decrements in sexual behavior than AME lesions. This is supported by the facts that there exists, overall, more significant correlations in CO activity between the NS and other hypothalamic and preoptic nuclei than between the AME and hypothalamic and preoptic nuclei, that glucose consumption is elevated in the NS in male redsided garter snakes during courtship [Allen and Crews, 1992], and that AME lesions do not significantly affect the expression of courtship behaviors in male anole lizards [Greenberg et al, 1984].…”
Section: Functional Connections and Sexual Behaviormentioning
confidence: 82%
“…AR mRNA was expressed at a high level within the medial preoptic area, the periventricular preoptic area, and the anterior hypothalamus, which is concordant with our previous finding that androgens activate copulatory behavior and tail vibrations (a male‐typical courtship behavior) in the leopard gecko (Rhen and Crews, 1999). Male garter snakes that display courtship behavior accumulate more 2‐deoxyglucose in the AH‐POA than noncourting males, which presumably reflects differences in neural activity associated with mating (Allen and Crews, 1992). The premammillary nucleus also was labeled intensely for AR mRNA in the leopard gecko.…”
Section: Discussionmentioning
confidence: 99%